2022
DOI: 10.1002/pros.24405
|View full text |Cite
|
Sign up to set email alerts
|

The state of PSA counseling in male‐to‐female transgender patients in the U.S.

Abstract: Background Morbidity and mortality from prostate cancer (PCa) are known to vary heavily based on socioeconomic and demographic risk factors. We sought to describe prescreening PSA (prostate‐specific antigen) counseling (PPC) rates amongst male‐to‐female transgender (MtF‐TG) patients and non‐TG patients using the behavioral risk factor surveillance system (BRFSS). Methods We used the survey data from 2014, 2016, and 2018 BRFSS and included respondents aged 40–79 years who completed the “PCa screening” and “sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Transgender participants in Ma et al's study were less likely to have PSA screening [35]. This is supported by findings from two additional studies that indicated that transgender women were less likely than cis-gendered men to ever have a risks versus benefits discussion about PSA screening with healthcare providers [38,39]. It is plausible that transgender women may find it challenging to disclose their personal sexual identity history to primary care physicians, leading to the possibility of not being offered the opportunity to talk about PSA screening when it is appropriate [5].…”
Section: Prostate Cancer Screening and Diagnosis In Sexual Minoritiesmentioning
confidence: 80%
“…Transgender participants in Ma et al's study were less likely to have PSA screening [35]. This is supported by findings from two additional studies that indicated that transgender women were less likely than cis-gendered men to ever have a risks versus benefits discussion about PSA screening with healthcare providers [38,39]. It is plausible that transgender women may find it challenging to disclose their personal sexual identity history to primary care physicians, leading to the possibility of not being offered the opportunity to talk about PSA screening when it is appropriate [5].…”
Section: Prostate Cancer Screening and Diagnosis In Sexual Minoritiesmentioning
confidence: 80%
“…Our analysis highlights baseline intersectional obstacles that heighten the disconnection between health care and transgender individuals . Specifically, transgender women had lower annual income, higher unemployment rates, lower educational attainment, and higher health care cost barriers compared with cisgender men, trends that are well-described in the literature . Given the profound effect of these factors on comorbid conditions and health care access, we matched cisgender men and transgender women by these sociodemographic factors to minimize confounding the effects of clinician-specific interactions .…”
Section: Discussionmentioning
confidence: 97%
“…15 Specifically, transgender women had lower annual income, higher unemployment rates, lower educational attainment, and higher health care cost barriers compared with cisgender men, trends that are well-described in the literature. 16 , 17 , 18 , 19 Given the profound effect of these factors on comorbid conditions and health care access, we matched cisgender men and transgender women by these sociodemographic factors to minimize confounding the effects of clinician-specific interactions. 12 , 20 It is well established that a significant barrier in transgender health care is lack of clinician competency, as most clinicians have little to no formal training in transgender care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation